The Goldwater Rule at 50 and its relevance in Europe: Examining the positions of National Psychiatric Association Members of the European Psychiatric Association - Alexander Smith; Stefanie Hachen; Moritz van Wijnkoop; Kolja Schiltz; Peter Falkai; Michael Liebrenz (European Psychiatry, 2023)
Abstract